The level of self-directed learning among teacher training institute students – an early survey - Kok, Boon Shiong; Aris, Baharuddin; Tasir, Zaidatun (Penerbit UTM Press, 2009)
Current learning approaches have various structured learning activities as well more self-directed learning tasks guided through consultation with academics. The aim of this research is to determine students’ self-directed learning readiness (SDLRS) in a Teacher Training Institute. 266 students from the Kursus Perguruan Lepasan Ijazah (KPLI), Program Ijazah Sarjana Muda Perguruan (PISMP) and Program Persediaan Ijazah Sarjana Muda Perguruan (PPISMP) group took part in the research. The instrument is a questionnaire adopted from Guglielmino SDLRS questionnaire. Result from the data analysis showed that most of the students are on average or below average in term of SDLRS. Based on SDLRS, there is also significant difference between gender with respect to self directed learning readiness. In addition, there ia also significant difference of students’ SDLRS with respect to their courses.